The Effects of Newcastle virus Histologically Suspension on Some Organs of White Mice (Balb /c) - Alaa Abd Alzahraa1, Ahmed Obaid Hossain1, Abbas Abd Sherhan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Newcastle disease is a contagious bird disease affecting wild avian species and many domestic,it may be transmissible to humans. Detection of Newcasstle virus confirmed by rapid test technique(Immunochromatography) . ten sample (10% ) out of 100 fasces sample collected from chickens were posative. Twelve mice used in this study devided into two groups ,first group consist of six mice induced with 0.2 ml from one positive sample of Newcasttle virus suspension to evaluate some histopathological changes caused by Newcasstle virus in small intestine and stomach of mice,second group induced with 0.2 ml from phosphate buffer saline only. The results revealed that histopathological changes in liver induced by using 0.2 ml from the positive Newcasstle virus suspension as hyperpalsia in kufper cells. Lung of mice treated with this concentration of Newcasstle virus has partial pnemonia and thicking the intra alveolar walls. While brain of mice treated with same concentration suffering from increase in number of glial cells ( glialosis ) and apoptosis in brain cells.